2013
DOI: 10.1038/nmeth.2283
|View full text |Cite
|
Sign up to set email alerts
|

Generation of integration-free neural progenitor cells from cells in human urine

Abstract: Human neural stem cells hold great promise for research and therapy in neural disease. We describe the generation of integration-free and expandable human neural progenitor cells (NPCs). We combined an episomal system to deliver reprogramming factors with a chemically defined culture medium to reprogram epithelial-like cells from human urine into NPCs (hUiNPCs). These transgene-free hUiNPCs can self-renew and can differentiate into multiple functional neuronal subtypes and glial cells in vitro. Although functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
182
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(190 citation statements)
references
References 43 publications
1
182
0
3
Order By: Relevance
“…In a single culture, these may include dopaminergic neurons marked by tyrosine hydroxylase (TH), glutamatergic neurons marked by vesicular glutamate transporter, interneurons marked by γ-aminobutyric acid, and motor neurons marked by choline acetyltransferase (Ambasudhan et al, 2011;Pang et al, 2011;Qiang et al, 2011;Yoo et al, 2011). In a similar way, neurons differentiated from iNPCs thus far also seem to contain multiple neuronal subtypes (Han et al, 2012;Ring et al, 2012;Wang et al, 2013;Zou et al, 2014). It is clear from these studies that the method of NPC production and the precise patterning cues that are provided have a direct bearing on the potential of the cells to reliably differentiate into specialized cell types.…”
Section: Specification Of Dg Granule Neurons In Vitromentioning
confidence: 99%
“…In a single culture, these may include dopaminergic neurons marked by tyrosine hydroxylase (TH), glutamatergic neurons marked by vesicular glutamate transporter, interneurons marked by γ-aminobutyric acid, and motor neurons marked by choline acetyltransferase (Ambasudhan et al, 2011;Pang et al, 2011;Qiang et al, 2011;Yoo et al, 2011). In a similar way, neurons differentiated from iNPCs thus far also seem to contain multiple neuronal subtypes (Han et al, 2012;Ring et al, 2012;Wang et al, 2013;Zou et al, 2014). It is clear from these studies that the method of NPC production and the precise patterning cues that are provided have a direct bearing on the potential of the cells to reliably differentiate into specialized cell types.…”
Section: Specification Of Dg Granule Neurons In Vitromentioning
confidence: 99%
“…Previous studies reported that TAF9B was dispensable for global gene expression and pluripotency of murine ESCs, but TAF9B was required for the efficient in vitro differentiation of murine ESCs into motor neurons (22). Moreover, it has been shown that epithelial-like cells from human urine can be reprogrammed into UiPSCs, and even directly into human neural progenitor cells (23,24). Therefore, our result may indicate that the level of TAF9B in UiPSCs would account for its preference towards neuron differentiation.…”
Section: Validation Of Differently Expressed Genes By Qrt-pcrmentioning
confidence: 53%
“…As a compromise, iNSCs/iNPCs can be obtained from the intermediate pluripotent cells during iPSC induction [53][54][55][56], by changing the medium to what can selectively support NSC growth. Pei and colleagues have managed to generate iNPCs from human urine epithelial-like cells by using this strategy [54]. These iNPCs exhibited primitive features with a good proliferative capacity, and could give rise to DA neurons in vitro [54].…”
Section: Induced Neural Stem Cells (Inscs)mentioning
confidence: 99%
“…Pei and colleagues have managed to generate iNPCs from human urine epithelial-like cells by using this strategy [54]. These iNPCs exhibited primitive features with a good proliferative capacity, and could give rise to DA neurons in vitro [54]. It remains unclear whether these cells are safe and/or efficacious in PD animal models.…”
Section: Induced Neural Stem Cells (Inscs)mentioning
confidence: 99%